[OP.8C.03] IMPROVED ENDOTHELIAL FUNCTION AND E-NOS EXPRESSION AND FUNCTION IN TRANSGLUTAMINASE-2 KNOCK-OUT MICE INFUSED WITH ANGIOTENSIN-II. (September 2016) - Savoia, C.; Arrabito, E.; Chiandotto, S.; Nicoletti, C.; Volpe, M.
Abstract : Objective: We previously demonstrated that transglutaminase-2 (TG2) may contribute to the angiotensin-II-induced vascular structural alterations. Here we hypothesized that TG2 may contribute to the impaired functional properties of resistance arteries from angiotensin-II-treated mice. Design and method: TG2-knockout mice (TG2-K/O, 8 weeks old, n = 6) and age-matched wild type (WT) control mice were treated or not with angiotensin-II (400 ng/kg/min) for 14 days. Blood pressure (BP) and heart rate were measured by tail-cuff method. Endothelium-dependent and –independent relaxations were assessed by concentration-response curves to acetylcholine (1 nM-to-100 μM) ± L-NAME (100 μM) and sodium nitroprusside (10 nM-to-1 mM) respectively, in mesenteric arteries pre-contracted with norepinephrine (10 μM). The expression of TG2, total eNOS, p-eNOS-(S1177), the negative modulator of eNOS (NOS-Interacting Protein, NOSIP) were evaluated in aorta by immunoblotting. TG2 activity in aorta and plasma nitrate/nitrate were measured by ELISA. Results: BP and heart rate were higher in TG2-K/O mice compared to WT (114.9 ± 0.7 mmHg vs 95.0 ± 1.0 mmHg, P < 0.001; and 633.1 ± 18.4 bpm vs 552 ± 16.7 bpm, P < 0.01, respectively). In both experimental groups, angiotensin-II infusion increased BP (+24% vs untreated WT, P < 0.001 and +11% vs untreated TG2-K/O, P < 0.001) and heart rate (+18% vs untreated WT, P < 0.001 and +11% vs untreated TG2-K/O, P < 0.01). TG2-K/O lacked TG2. Angitensin-II significantly increased (2-fold) TG2 expression and activity only in WT. Endothelium-dependent relaxation was similarly preserved in untreated WT, TG2-K/O and angiotensin-II-treated TG2-K/O. Angiotensin-II infusion impaired acetylcholine-induced relaxation only in WT (−21% vs untreated WT, P < 0.05). L-NAME blunted acetylcholine induced relaxation in all the groups except in angiotensin-II-treated WT, suggesting an impairment of NO production only in this group. Endothelium-independent relaxation was similar in all groups. Basal plasma nitrates/nitrates were similar in WT and TG2-K/O; angiotensin-II significantly reduced plasma nitrates/nitrates only in WT (−37.2%). p-eNOS-(S1177)/eNOS was similar in WT and TG2-K/O. Angiotensin-II significantly reduced p-eNOS-(S1177)/eNOS only in WT (−38%). NOSIP was similar in both WT and TG2-K/O and was significantly reduced by angiotensin-II only in TG2-K/O (−27%). Conclusions: Despite BP increase angiotensin-II failed to impair endothelial function and reduce NO bioavailability and e-NOS expression and function in TG2-K/O. Thus, TG2 may contribute to endothelial dysfunction in resistance arteries of angiotensin-II infused mice.